Cancer stem cells: the promise and the potential - Ajani, Jaffer A; Song, Shumei; Hochster, Howard S; Steinberg, Ira B (Seminars in oncology, 2015)
Despite the advancement of treatment modalities, many cancer patients experience tumor recurrence and metastasis at regional or distant sites. Evolving understanding of tumor biology has led to the hypothesis that tumors may possess a stem cell-like subpopulation known as cancer stem cells (CSCs) that may be involved in driving tumor propagation and pathogenesis. Like normal stem cells (NSCs), CSCs can be identified by markers such as CD133, CD44, and ALDH. CSCs have the ability to self-renew and differentiate into different tumor components through stemness pathways, such as Wnt, TGF-β, STAT, and Hippo-YAP/TAZ, among others. In NSCs, stemness pathways are strictly regulated and control many important biologic processes, including embryogenesis and intestinal crypt cellular regulation. In contrast, stemness pathways in CSCs are significantly dysregulated. Combining current drugs with the targeting of these stemness pathways may significantly improve patient prognosis. The aim of this supplement is to update clinicians on the accumulated evidence characterizing the role of CSCs in tumor initiation, heterogeneity, therapy resistance, and recurrence and metastasis, and the potential for effectively treating patients.